The Activity Activation Function Of Multilayer Perceptron - Based Cardiac Abnormalities: The Activity Activation Function Of Multilayer Perceptron - Based Cardiac Abnormalities - Mutiara S. Simanjuntak; Wanayumini Wanayumini; Rika Rosnelly; Teddy Surya Gunawan (Institute of Computer Science (IOCS), 2020)
Cardiac disorders refer to irregular activity at the heart. Cardiac abnormalities sometimes do not exhibit any and unreasonable symptoms that can lead to sudden death due to heart-cracking functions. This article is to develop a program capable to detect cardiac abnormalities activity through the application of Multilayer Perceptron (MLP). A certain number of heart rate signal data from an electrocardiogram (EKG) will be used in this paper to train and to test the network performance of the MLP. MLP is trained by several techniques that Backpropagation (BP), Bayesian regularity (BR), and Levenberg-Marquardt (LM).